The Development of Teaching Media Based on Interactive Multimedia towards Economic Courses to Enhance Students’ Learning Outcomes at Senior High School - Windy Safitri; Dessi Susanti (AL-ISHLAH: Jurnal Pendidikan, 2023)
Interactive multimedia assists teachers in bringing the outside world into the classroom. Abstract and unfamiliar ideas become concrete and easy to understand by students, so if financial accounting subjects are delivered using interactive multimedia, abstract financial accounting concepts will be easy to convey. This research aims to produce interactive multimedia that is valid, practical and effective for use in economic learning activities. The research method used is Research and Development with the ADDIE development model which includes: 1) Analysis Phase; 2) Design Stage; 3) Development Stage; 4) Implementation Stage; and 5) Evaluation Stage. This research was carried out at one of the state high schools in Medan City. Product validation is carried out by a validator each for material experts and media experts. The research sample was all class XI students. Research instruments include interview sheets, observation sheets, validation sheets, practicality sheets, and test sheets. The research results show that the use of interactive multimedia in economic learning activities has proven to be valid, practical and effective in improving student learning outcomes.